Civil Law Review on Crypto Investment and Consumer Risks - Sunarto, Atika; Adnan, Muhammad Ali; Khair, Azizan (Arena Hukum, 2025)
Cryptocurrency is rapidly developing as a new digital investment instrument in Indonesia, yet the reliability of the Indonesian civil law framework in protecting consumers remains uncertain. This study aims to investigate: to what extent does Indonesian civil law provide adequate legal protection to consumers engaged in cryptocurrency investment activities? This issue is urgent due to high price volatility, market manipulation risks, and weak legal certainty for investors. Previous studies, such as Rere (2024), focused on criminal aspects of digital asset fraud, while Zain (2025) examined trade regulations under Bappebti’s supervision. However, neither fully explores the civil law protection for consumers as investors. This research assesses the effectiveness of civil law in ensuring legal safeguards for cryptocurrency investors. The method employed is a normative juridical approach, utilising a literature study as the primary method. The findings reveal that existing regulations, particularly Bappebti Regulation No. 5 of 2019, are still limited to technical trading aspects and business actor oversight, lacking substantive provisions on civil liability for consumer losses. This study contributes to legal scholarship by advocating for regulatory reform that strikes a balance between digital innovation and consumer protection. For international readers, the article provides insights into how developing countries address legal challenges related to cryptocurrency investments and stimulates comparative legal discourse on digital consumer protection across jurisdictions.